Peran Etika dan Hukum Bisnis dalam Mendorong Keberlanjutan Usaha Mikro, Kecil, dan Menengah - Putri, Ramanitya Dewi; Reza, Saru (EL-EMIR Institute, 2025)
This study aims to analyze the role of business ethics and law in promoting the sustainability of Micro, Small, and Medium Enterprises (MSMEs). The sustainability of MSMEs is a crucial issue given their strategic role in the national economy, yet they still face various challenges, particularly the low level of ethical implementation and compliance with business law. The research method used was a qualitative approach with library research. Data were obtained from various secondary sources, including textbooks, national and international journal articles, official agency reports, and laws and regulations relevant to business ethics, business law, and MSMEs. The collected data were analyzed using descriptive-analytical content analysis. The results indicate that business ethics plays a crucial role in shaping business behavior with integrity, increasing consumer trust, and creating harmonious working relationships, thus positively contributing to the sustainability of MSMEs. Meanwhile, business law provides legal certainty and protection that support business stability and development. The synergy between business ethics and law has proven to be a key factor in realizing MSMEs that are competitive and economically, socially, and environmentally sustainable.